Factors associated with self-reported ill health among older Ugandans: A cross sectional study - Ojiambo Wandera, Stephen; Golaz, Valerie; Kwagala, Betty; Ntozi, James (Archives of gerontology and geriatrics, 2015)
There is limited research on the prevalence and factors associated with self-reported ill health among older people in Uganda. Objective: Therefore, the aim of this paper was to estimate the prevalence of self-reported ill health and to identify associated risk factors among older people (age 50+) in Uganda. Materials and methods: We conducted secondary analysis of a cross sectional survey data from a weighted sample of 2382 older persons from the 2010 Uganda National Household survey. We used frequency distributions for descriptive statistics, chi-square tests (significance set at 95%) to identify initial associations and multivariable logistic regressions reporting odds ratios to examine observed associations with self-reported ill health. Results: Over half (62%) of the older people reported ill health in the 30 days preceding the survey. Selfreported ill health was positively associated with being a woman, being among the oldest old, living in the eastern region, being a household head, being Catholic, self-reported non-communicable diseases (NCDs) and being disabled.
Keywords: Sub-Saharan Africa; Uganda; Elderly Health status; Self-rated health